Wavepackets in turbulent flow over a NACA 4412 airfoil - Abreu, Leandra I.; Cavalieri, André V.G.; Schlatter, Philipp; Vinuesa, Ricardo; Henningson, Dan (31st Congress of the International Council of the Aeronautical Sciences, ICAS 2018, 2018)
Turbulent flow over a NACA 4412 airfoil with an angle of attack AoA = 5 ◦ was analysed using an incompressible direct numerical simulation (DNS) at chord Reynolds number of Re c = 4 · 10 5 . Snapshots of the flow field were analysed using the method of Spectral Proper Orthogonal Decomposition (SPOD) in frequency domain, in order to extract the dominant coherent structures of the flow. Focus is given to two-dimensional disturbances, known to be most relevant for aeroacoustics. The leading SPOD modes show coherent structures forming a wavepacket, with significant amplitudes in the trailing-edge boundary layer and in the wake. To model coherent structures in the turbulent boundary layer, the optimal harmonic forcing and the associated linear response of the flow were obtained using the singular value decomposition of the linear resolvent operator. The resolvent analysis shows that the leading SPOD modes can be associated to most amplified, linearised flow responses. Furthermore, coherent structures in the wake are modelled as the Kelvin-Helmholtz mode from linear stability theory (LST).
CRIS-Team Scopus Importer:2023-03-21
Keywords: Coherent structures; Reduced order models; Resolvent analysis; SPOD; Wavepackets